2018
DOI: 10.14236/jhi.v25i4.1068
|View full text |Cite
|
Sign up to set email alerts
|

Five key strategic priorities of integrating patient generated health data into United Kingdom electronic health records

Abstract: The integration of patient/person generated health data into clinical applications is a widespread aspiration internationally. However, there is still a range of challenges that inhibit progress in this area. These include technology-related factors (such as interoperability), use-related factors (such as data overload) and characteristics of the strategic environment (such as existing standards). Building on important policy deliberations from the United States that aim to navigate these challenges, we here a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Using PROMs to measure outcomes of using PGHD has been suggested 9. PROMs allow for a more holistic evaluation of the effects of various health services and interventions 4.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using PROMs to measure outcomes of using PGHD has been suggested 9. PROMs allow for a more holistic evaluation of the effects of various health services and interventions 4.…”
Section: Discussionmentioning
confidence: 99%
“…PGHD are created, recorded and analysed by people, who are monitoring their health outside of a clinical care setting. They include health, wellness and other biometric data produced from technologies such as mobile applications, activity tracking devices and simulated rehabilitation technologies 7–9. Utilisation of PGHD by patients promotes participatory health, as it has been suggested to increase their engagement, improve health management coordination with their care providers and increase their sense of social support and connectedness 10–15.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 16 Using PROMs has also been suggested as a way to standardise the measurement of PGHD outcomes and strengthen the empirical evidence around PGHD. 3 PROMs allow people to self-report their health status or experience with an illness or treatment, without the need for additional clinician interpretation of the report. [17][18][19] A patient-reported outcome may indicate status at a single point of time, or be compared with previous patientreported outcomes to show changes over time.…”
Section: What Does This Paper Add?mentioning
confidence: 99%
“…People may also record and analyse their PGHD for themselves, which includes wellness and other biometric data. [1][2][3] It has been reported that people who use PGHD have changes in their engagement with their own healthcare, their relationship with their healthcare providers and their sense of social support and connectedness. [4][5][6][7][8][9][10][11] Thus, PGHD utilisation promotes participatory health.…”
Section: Introductionmentioning
confidence: 99%